PERSEPSI MASYARAKAT CIMANDE MENGENAI SERVICE EXCELLENCE PADA PRIA DAN WANITA TERHADAP LOYALITAS NASABAH - Sarah, Arfiani; Paramita, Metti (NISBAH: JURNAL PERBANKAN SYARIAH, 2018)
This study aims to find out how cimande community perception about service excellence in men and women to customer loyalty (study at BTPN Syariah KCP Ciawi). In this study using descriptive quantitative and using anlisis method Likert Scale and Chi Square. Primary data was taken using questionnaire method with sampling using Slovin method as much as Fifty (50) samples from BTPN Syariah KCP Ciawi customer. This study aims to find out how cimande community perception about service excellence in men and women to customer loyalty (study at BTPN Syariah KCP Ciawi). In this study using descriptive quantitative and using anlisis method Likert Scale and Chi Square. Primary data was taken using questionnaire method with sampling using Slovin method as much as Fifty (50) samples from BTPN Syariah KCP Ciawi customer. The result of calculation of Chi Square test shows the difference of perception of society cimande about service excellence in man and woman to customer loyalty, this is indicated by value of chi square result 25,480 which concludes that H_0 is rejected and H_1 accepted means that society cimande agree There are different service excellence in men and women to customer loyalty.Keywords: public perception, service excellence, customer loyalty